INFLUENCE APPLICATION THEORY STUDY CONSTRUCTIVISM AND PRINCIPLES LEARNING EDUCATION ISLAM - Adi Kusuma; Fajri Ismail, Muhammad Win Afgani, Karoma, Mardiah Astuti (ADISAM Publisher, 2023)
The aims of this study were: 1) Describe the constructivism learning theory of students in Islamic religious education subjects. 2) Describe the principles of Islamic religious education for students in Islamic religious education subjects. 3) Describing students' learning interest in the subject of Pekerti Islamic Religious Education. 4) Testing the effect of constructivism learning theory on students' learning interest in Islamic Religious Education subjects. 5) Testing the effect of the principles of Islamic religious education learning on students' learning interest in Islamic Religious Education subjects. 6) Testing the influence of constructivism learning theory together. The implication for students is to be able to increase interest in learning by reducing the habit of constructivist learning theory by means of good time management and setting priority scales for an activity, as well as increasing the principles of learning Islamic religious education so that they are brave in facing assignments with full responsibility and researchers. Furthermore, those who are interested in conducting research on academic procrastination, the principles of learning Islamic religious education and learning achievement, are advised to pay attention to other factors such as difficulty making decisions, fear of failure and several other factors.